Primary Lymphoma of the Liver: A Case Report and Review - Franzjosef Schweiger; Rowen Shinder; Sheldon Rubin (Canadian Journal of Gastroenterology)
The case of a previously healthy man who developed primary non-Hodgkin’s lymphoma of the liver is presented. Biopsy confirmed that the tumour was of the diffuse large cell type and was of apparent T-cell origin. The diagnosis of these rare tumours is suggested by the presence of a hepatic mass without lymphadenopathy, splenomegaly or bone marrow involvement, as well as normal carcinoembryonic antigen and alpha-fetoprotein levels. However, histological examination of tissue is essential to confirm the diagnosis. The response to treatment varies, but surgical resection and/or chemotherapy can result in prolonged remissions. The literature on this topic is briefly reviewed.